2009
DOI: 10.1111/j.1574-6968.2008.01484.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effects of positive charge and hydrophobicity on the cell selectivity, mechanism of action and anti-inflammatory activity of a Trp-rich antimicrobial peptide indolicidin

Abstract: To investigate the effects of positive charge and hydrophobicity on the cell selectivity, mechanism of action and anti-inflammatory activity of a Trp-rich antimicrobial peptide indolicidin (IN), a series of IN analogs with Trp-->Lys substitution were synthesized. All IN analogs displayed an approximately 7- to 18-fold higher cell selectivity, compared with IN. IN, IN-1 and IN-2 depolarized (50-90%) the cytoplasmic membrane potential of Staphylococcus aureus close to minimal inhibitory concentration (5-10 micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 27 publications
(27 reference statements)
2
34
0
Order By: Relevance
“…PheTrp substitutions in C1-15, resulting in peptide F2,5,12W, significantly increased the LPS-neutralising capacity. Recently, we [11] and others [12] reported the importance of hydrophobicity in neutralising LPS cytokine responses. In line with our observations, Nan et al [12] showed that substitution of Trp by Lys residues in the Trp-rich peptide indolicidin resulted in decreased hydrophobicity and loss of LPS-neutralising activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PheTrp substitutions in C1-15, resulting in peptide F2,5,12W, significantly increased the LPS-neutralising capacity. Recently, we [11] and others [12] reported the importance of hydrophobicity in neutralising LPS cytokine responses. In line with our observations, Nan et al [12] showed that substitution of Trp by Lys residues in the Trp-rich peptide indolicidin resulted in decreased hydrophobicity and loss of LPS-neutralising activity.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we [11] and others [12] reported the importance of hydrophobicity in neutralising LPS cytokine responses. In line with our observations, Nan et al [12] showed that substitution of Trp by Lys residues in the Trp-rich peptide indolicidin resulted in decreased hydrophobicity and loss of LPS-neutralising activity. Previously it was shown that inhibition of the pro-inflammatory response is mainly established by direct binding of cationic HDPs to LPS [11,13].…”
Section: Discussionmentioning
confidence: 99%
“…The hydrophobicity and isoelectric point of the peptide variants were analyzed (Table 1), as a number of studies have reported a correlation between both parameters and antimicrobial activity (23)(24)(25)(26). However, no significant link between either parameter and activity could be observed for our collection of variants.…”
Section: Discussionmentioning
confidence: 99%
“…The hydrophobicity of the caseicin variants was also analyzed, as a number of studies have discovered a correlation between hydrophobicity and antimicrobial activity (2,16,21). Unfortunately, we could not link antimicrobial activity with the percent hydrophobicity of the variant caseicins.…”
Section: Discussionmentioning
confidence: 99%